Mate selection preferences of older adolescent children of intact and non-intact marriages focus on psychosocial traits - Alejandre, Maria Cristina M.
The present study identified, described and determined the similarities and differences of the mate selection preferences of older adolescent children of intact and non-intact marriages, focusing on the psychosocial traits. Fifty three male and female students of the University of the Philippines-Diliman from intact and non-intact marriages, aged 16-19 years old, were purposively selected to answer questionnaires. Six males and six females among the survey respondents from both maritl structures were asked to participate in a small group discussion. Data obtained from these two methodologies were analyzed using frequency tables, non parametric correlations (Kendall's Tau_b and Spearman's Rho), and Analysis of Variance and Multiple Regression Analysis. Results showed that some psychosocial aspects of the mate preferences had significant correlation to the structure of marriage. In their most preferred psychosocial trait, adolescents from non-intact marriages significantly valued the emotional aspect. Meanwhile, adolescents from intact marriages considered the other three aspects of psychosocial trait namely; economic, moral, and social. In terms of least preferred traits, adolescents from intact marriages gave importance to economic aspect while the adolescents from non-intact marriages gave weight on the emotional, moral and social aspects. Differences are said to be brought out by unique family experiences.